Restorative Justice: Finding Common Ground Between Justice and Shared Interests - Yustia, Dewi Asri; Jodi, Faris Fachrizal; Panjaitan, Ananda Chrisna D.; Hassan, Fareed Mohd (Universitas Negeri Gorontalo, 2026)
In Indonesia’s current criminal justice practice, the resolution of criminal acts can be pursued through two main approaches: retributive justice, as regulated by the Indonesian Criminal Procedure Code (KUHAP), and restorative justice, which has gradually been adopted through various regulations at the stages of investigation, prosecution, and adjudication. Restorative justice emphasizes restoration rather than retribution by involving the offender, the victim, their respective families, and community figures in a collaborative process to reach a fair resolution. This study aims to examine the fundamental principles of restorative justice within the Indonesian criminal justice system and to propose a conceptual framework that promotes an integrative approach to resolving criminal cases by balancing the interests of all parties. Using a normative juridical method and a qualitative approach, the study finds that restorative justice is based on the principles of restitution, reconciliation, and social reintegration. To support its effective implementation, the concept should include the strengthening of legal norms concerning victims’ rights, the authority of law enforcement institutions, and the development of a justice system that embraces restorative values. Ultimately, the application of restorative justice is expected to shape a criminal justice system that is not only repressive but also ensures a balanced consideration of the interests of victims, offenders, and society as a whole.